Entertainment gratification, informative gratification, web irritation and self-efficacy as motivational factors to online shopping intention / Norol Hamiza Zamzuri ... [et al.] - Zamzuri, Norol Hamiza; Kassim, Erne Suzila; Shahrom, Melissa; Humaidi, Norshima (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
The Internet technology and pervasive computing has provided consumers with privileges to shop online. In addition, the Industry 4.0 agenda has placed the business web and the social web as the ecosystem domains, which explains why online shopping is a norm today. While many studies have been conducted to investigate the determinants of consumers’ intention to use online shopping, mixed results are always found, especially when the business take unique approaches for their digital presence. Besides, even though self-efficacy has been studied extensively in information system research, technological complexity has always given a challenge to consumers’ computing ability. Building on the Use and Gratification Theory (GTA) and the Social Cognitive Theory (SCT), this study aims to examine the relationships between entertainment gratification, informative gratification, web irritation and self-efficacy towards individual’s intention to use online shopping. Using the quantitative survey approach, data was collected from 217 young executives who are frequent online shoppers. The results of the structural equation modeling suggest entertainment gratification, informative gratification and self-efficacy are the factors that derive consumers’ intention to shop online. On the other hand, web irritation has no significant relationship with online shopping intention. The findings do not only capture the importance for web retailers to provide adequate buying-selling information and to provide the element of fun to the shopping portals, but it also suggests for the web retailers to provide less complicated online shopping features since consumers’ ability to use the technology determines purchase behavior. The findings serve as future research agenda.